Wilson loop's phase transition probed by non-local observable - Hui-Ling Li; Zhong-Wen Feng; Shu-Zheng Yang; Xiao-Tao Zu (Nuclear Physics B, 2018)
In order to give further insights into the holographic Van der Waals phase transition, it would be of great interest to investigate the behavior of Wilson loop across the holographic phase transition for a higher dimensional hairy black hole. We offer a possibility to proceed with a numerical calculation in order to discussion on the hairy black hole's phase transition, and show that Wilson loop can serve as a probe to detect a phase structure of the black hole. Furthermore, for a first order phase transition, we calculate numerically the Maxwell's equal area construction; and for a second order phase transition, we also study the critical exponent in order to characterize the Wilson loop's phase transition.